Diode-Pumped 50 Hz–10 J Nano-Second Nd:YAG Laser - Jiang, Xinying; Xiao, Kaibo; Yan, Xiongwei; Wang, Zhenguo; Jiang, Xuejun; Xue, Qiao; Wu, Wenlong; Chen, Ji; Zhang, Chuanchao; Zheng, Jiangang; Peng, Zhitao; Zheng, Kuixing; et al. (Frontiers in Physics, 2022)
In this letter, we report a diode pumped nano- second laser with the output energy 10J, repetition rate 50Hz and the average power 500W. The main amplifier was made up by 8 amplify modules. Each amplify module was pumped by 808nm laser diode and cooled by water from the back end of Nd:YAG slab. To our knowledge, this represents the highest pulse repetition rate for 10J class nano-second single aperature Nd:YAG laser. The beam quality was controlled by means of mechanical design and adjustment and compensation by a home-made deforming mirror. The beam quality was controlled well with the beam quality of the laser 2.61DL.